2011
DOI: 10.1242/jcs.078535
|View full text |Cite
|
Sign up to set email alerts
|

The non-receptor tyrosine kinase Lyn controls neutrophil adhesion by recruiting the CrkL–C3G complex and activating Rap1 at the leading edge

Abstract: Research Article 2153 IntroductionCell migration has been conceptualized as a cycle (Ridley et al., 2003). After a stimulus, cells polymerize actin at the front to initiate protrusions. These protrusions are stabilized by adhering to extracellular matrix (ECM) molecules (adhesion). Adhesions serve as traction sites as the cell moves forward, and are disassembled at the rear, allowing the cell to detach and retract. In general, strategies for single-cell migration can be classified into two patterns: amoeboid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Although it has been reported that active β2-integrins localize to the leading edge of differentiated HL-60 cells (He et al ., 2011), consistent with earlier findings (Pierini et al ., 2000), we found that active β2-integrins appear in punctates that do not colocalize with F-actin and are generally enriched in the back of polarized primary human blood neutrophils and differentiated PLB-985 cells. Of importance, polarized PLB-985 cells overexpressing Radil show a significant increase in fluorescent signal of active β2-integrins at their back.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although it has been reported that active β2-integrins localize to the leading edge of differentiated HL-60 cells (He et al ., 2011), consistent with earlier findings (Pierini et al ., 2000), we found that active β2-integrins appear in punctates that do not colocalize with F-actin and are generally enriched in the back of polarized primary human blood neutrophils and differentiated PLB-985 cells. Of importance, polarized PLB-985 cells overexpressing Radil show a significant increase in fluorescent signal of active β2-integrins at their back.…”
Section: Discussionmentioning
confidence: 98%
“…Rap1a-deficient neutrophils have been generated (He et al ., 2011) and, much like what we observed with our Radil-knockdown cells, shown to exhibit decreased adhesion on fibrinogen-coated plates. Of interest, these authors observed that Rap1a-depleted neutrophils retract slowly and show spindle-shaped morphology during chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the signal is transmitted from the G protein to Rap1 is not known, although several candidates have emerged. In HL-60 cells, fMLP activates a non-RTK Lyn in a G i protein-dependent manner [230]. Lyn recruits and activates the adaptor protein CrkL, which constitutively associates with a Rap1 GEF C3G.…”
Section: Chemotactic Network Of Dictyostelium and Leukocytesmentioning
confidence: 99%
“…The Crk-SH3N, which mediates C3G binding, plays an important role in this process, because expression of a SH3N-defective mutant inhibited cell adhesion to fibronectin (44)(45)(46). In addition, both Crk and C3G function as focal adhesion proteins and Crk-C3G complexes recruit to the leading edge of polarized cells, where they activate additional effector molecules and provide spatially instructive cues required for cell adhesion and migration (47)(48)(49)(50).…”
Section: Treatment Of Picchux-transfected Jurkat T Cells With Csa Plumentioning
confidence: 99%